Radiocarbon dating insect samples: new data and recommendations - Briant, Rebecca M.; Ascough, Philippa L.; Brock, Fiona; Smith, David N. (Taylor & Francis, 2025)
Radiocarbon dating insects is difficult because insects are small, fragile, and rarely found in sufficient quantities. Interactions between the chitin in the insect body and sources of carbon contamination are less well understood than for collagen and cellulose-based organic materials such as bone and plant remains. Thus there is as yet no single radiocarbon pretreatment that reliably removes all contaminating carbon across all types of insect remains. Various studies have highlighted important information concerning the practicalities and applicability of different approaches to radiocarbon dating insect remains. However, there are no papers that synthesise findings across different studies. Here, we present a review of previous work alongside new data to investigate different chemical approaches to sample processing and long-term storage and their impact on the chemistry of samples and contaminants. This confirms the difficulty of removing contamination from older samples while retaining sufficient pretreated material for subsequent measurement. It also shows that Fourier transform infrared (FTIR) spectroscopy does not always provide sufficient resolution to detect carbon contamination from non-insect sources with confidence. Thus, insect samples that have been in contact with paraffin or stored in ethanol for an extended period of time should not be selected for radiocarbon dating.
Keywords: 3103 Ecology; 4301 Archaeology; Radiocarbon dating; insects; chitin; environmental archaeology; chemical pretreatment; fourier transform infrared spectroscopy (FTIR)